PENINGKATAN PERILAKU INOVATIF MELALUI BUDAYA ORGANISASI - Bondan Ndaru Prayudhayanti (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2014)
Human resources is a very important factor as a driver in the face of global current era. The competitiveness of an organization depends on human resources owned. Particularly associated with either organizational commitment and innovative behavior. This study aims to analyze the innovative behavior of the teachers SMK Negeri I Bawen Semarang District. Variables used in this study is to use a variable of organizational culture and job satisfaction. Organizational culture and job satisfaction serves as an independent variable in analyzing the behavior of innovative teachers of SMK Negeri I Bawen Semarang District. Besides other variables used in this penelian organizational commitment is a variable that serves as an intervening variable. Sampling technique used in this study is to use the census method with a number of respondents as much as 78 teachers at SMK Negeri I Bawen Semarang District. Teknik of analysis data used in this study using analysis techniques Smart PLS (Partial Least Squere). The results of this study indicate that the variable organizational culture and job satisfaction has a positive and significant impact on organizational commitment. variables of organizational culture, job satisfaction and organizational commitment also showed a positive and significant impact on the performance of teachers.Key words: organizational culture, job satisfaction, organizational commitment andinnovative behavior.